Creating appropriate online learning environments for female health professionals - Pinheiro, Marise; Campbell, Katy; Hirst, Sandra; Krupa, Eugene (Canadian Journal of Learning and Technology, 2006)
In this study, the experiences of seven female health professionals learning online are examined and, in this context, the implications for online course designs and future research are discussed. The instruments of data collection include individual telephone interviews, journals written by the participants during online courses, and e-mails exchanged by the participants and researcher. The principles of qualitative research are integrated into the process of collecting and analyzing the data. Participants identified lack of face-to-face interaction and overload of work as major challenges to learning online. Increase in confidence and the opportunity to belong to a community of learners were cited as rewards of learning online. In addition, the participants identified preferences for contextual and experiential learning, and for learning environments that foster collaboration. Participants agree that interacting with other classmates, building local support, and developing a mentoring relationship with instructors are key aspects of a successful learning experience.